2019
DOI: 10.29252/ijmr-060206
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus gasseri as a Functional Food and Its Role in Obesity

Abstract: Introduction Obesity is a chronic, relapsing, progressive disease. It is identified by abnormal and excessive fat accumulation which is defined as a body mass index (BMI) higher than 25 kg/m 2. 1 The health risks of obesity include a wide range of medical, surgical, gynecological, obstetric, social, and psychological conditions such as hypertension, cerebrovascular incidents, cancers, hyperlipidemia, coronary heart disease, diabetes mellitus, and degenerative arthritis. 2 Therefore, the costs imposed by obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, our research demonstrated that treatment of BNR17 resulted in the increased body weight in stress-T2D. However, other studies demonstrated that BNR17 showed the beneficial effects of weight loss in obesity and T2D [ 54 , 55 ]. In general, stresses that are regulated by HPA and corticosterone are related with body weight, but chronic stress may show weight gain and abdominal obesity [ 56 ].…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, our research demonstrated that treatment of BNR17 resulted in the increased body weight in stress-T2D. However, other studies demonstrated that BNR17 showed the beneficial effects of weight loss in obesity and T2D [ 54 , 55 ]. In general, stresses that are regulated by HPA and corticosterone are related with body weight, but chronic stress may show weight gain and abdominal obesity [ 56 ].…”
Section: Discussionmentioning
confidence: 54%
“…Gram-positive lactic acid bacteria generate lactic acid, are resistant to acid, and do not sporulate [16]. Several species of potentially probiotic microbes found are Lacticasei bacillus reuteri, Lacticasei bacillus casei, Lacticasei bacillus casei LA1, Lacticasei bacillus rhamnosus GG, Lactiplanti bacillus plantarum 299, and Lactobacillus gasseri are a few of them to have been used in a variety of therapeutic applications [17].…”
Section: Probiotic Strainmentioning
confidence: 99%
“…Several species of potentially probiotic microbes found are Lacticasei bacillus reuteri, Lacticasei bacillus casei, Lacticasei bacillus casei LA1, Lacticasei bacillus rhamnosus GG, Lactiplanti bacillus plantarum 299, and Lactobacillus gasseri are a few of them to have been used in a variety of therapeutic applications [17]. Among them, a native and indigenous human intestine LAB that is homofermentative, acid-resistant, and bile-tolerant is Lactobacillus gasseri [16]. Due to its ability to stick to intestinal tissues, activate macrophages, and create bacteriocins that can lower harmful microbes, it is commonly linked to probiotic effects.…”
Section: Probiotic Strainmentioning
confidence: 99%
“…In addition, previous studies have found that L. gasseri was associated with weight loss and the management of obesity. 12 However, establishment and persistence in the gut are vital for probiotics to exert their beneficial effects. 13 Competition for ecological niches has become one of the main issues limiting the application of probiotics.…”
Section: Introductionmentioning
confidence: 99%